2013
DOI: 10.1373/clinchem.2012.191700
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Individual Variation in Cardiac Troponin in Patients with Stable Coronary Artery Disease

Abstract: BACKGROUND A rise or fall of cardiac troponin is a prerequisite for the diagnosis of acute myocardial infarction. Defining significant changes requires knowledge of both biological and analytical variation. The short-term biological variation of cardiac troponin in healthy individuals is 3%–48%. However, healthy individuals may not be representative for patients in whom cardiac troponin measurement is often of clinical importance. Therefore, we studied the individual variation of cardiac trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 29 publications
9
41
0
Order By: Relevance
“…The weekly and monthly within-person variation of hs-cTnT estimated from dialysis patients in this study was markedly smaller than corresponding values reported for healthy individuals (15% and 31%, respectively) [30], but similar to those reported for non-dialysis dependent individuals with coronary artery disease (7.3% at 4-hourly intervals and 10.7% at 3-weekly intervals) [31]. These findings are likely explained by the fact that both dialysis patients and non-dialysis dependent patients with coronary artery disease have baseline troponin-T concentrations around or exceeding the 99th centile upper reference limit of the hs-cTnT assay [16,31] whereas healthy individuals have much lower baseline values [11].…”
Section: Impact Of Dialysis Therapy and Cardiac Co-morbidity On Biolosupporting
confidence: 62%
“…The weekly and monthly within-person variation of hs-cTnT estimated from dialysis patients in this study was markedly smaller than corresponding values reported for healthy individuals (15% and 31%, respectively) [30], but similar to those reported for non-dialysis dependent individuals with coronary artery disease (7.3% at 4-hourly intervals and 10.7% at 3-weekly intervals) [31]. These findings are likely explained by the fact that both dialysis patients and non-dialysis dependent patients with coronary artery disease have baseline troponin-T concentrations around or exceeding the 99th centile upper reference limit of the hs-cTnT assay [16,31] whereas healthy individuals have much lower baseline values [11].…”
Section: Impact Of Dialysis Therapy and Cardiac Co-morbidity On Biolosupporting
confidence: 62%
“…Normal biomarker concentrations without relevant increases, in contrast, might support clinicians in their decisions about not starting or even stopping medications with potentially harmful side-effects, a relevant issue in elderly populations. The appropriate timing of repeat measurements, however, remains to be determined, also taking the biologic variability of these biomarkers into account (34,35 ). For GDF-15, these recommendations are not similarly straightforward given the association of this biomarker with both CV and non-CV conditions (5,10,14,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Another important, measurable parameter is the inter-individual variation, which reflects biological variations among healthy individuals from a defined population. A number of investigators measured intraand inter-individual variations using various cTn assays [15,[55][56][57][58][59][60]. The results ranged from 4% to 30% for intraindividual variations and from 30% to 200% for interindividual variations as summarized by Nordenskjöld and coworkers [60].…”
Section: What Constitutes the Rise And/or Fall In Ctn Concentrations?mentioning
confidence: 97%